2019
DOI: 10.21315/mjms2019.26.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Does Overnight Culture of Cleaved Embryos Improve Pregnancy Rate in Vitrified-Warmed Embryo Transfer Programme?

Abstract: Background Vitrification is a routine procedure in assisted reproductive technique (ART) lab. However, there is widespread variability between protocols of different centres. The aim of this study was to compare the chemical pregnancy, clinical pregnancy and live birth rates between one-day embryo culture and immediate transfer for frozen-thawed embryo transfer (FET) cycles. Methods In this cohort retrospective study, 366 FET cycles were divided into two groups: Group A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Agha-Rahimi et al ( 11 ) included 366 frozen embryo transfers after vitrification in a retrospective cohort study. They reported a high chemical pregnancy rate in patients included in the overnight culture group when compared to the short culture time group.…”
Section: Discussionmentioning
confidence: 99%
“…Agha-Rahimi et al ( 11 ) included 366 frozen embryo transfers after vitrification in a retrospective cohort study. They reported a high chemical pregnancy rate in patients included in the overnight culture group when compared to the short culture time group.…”
Section: Discussionmentioning
confidence: 99%
“…Although Veleva et al and Agha-Rahimi et al concluded that no benefit of overnight culture on the cycle outcome and attributed this to the non-improvement of the quality of embryo with culture, nevertheless, they reported that it facilitated the best embryo selection to be transferred. Also, Veleva reported an important confounder in his study which was significantly higher implantation rate with D3 top-quality ET in relation to D2 top-quality ET, this was not the same with non-top-quality embryos and recommended further research to clarify such issue [27,44]. This actually was answered in this study that documented the role of extended culture of cleaved embryo to blastocyst stage in improving frozen cycle outcome.…”
Section: Discussionmentioning
confidence: 71%
“…They determined this synchronization with respect to the day of menstrual cycle (30). We recently showed that overnight culture before the transfer of warmed embryo is not essential for FET cycles (31). Therefore, our study suggested that at the time of embryo thawing, attention should be given to the day of embryo and the number of days of progesterone administration.…”
Section: Discussionmentioning
confidence: 76%